Over application courier company (DHL) to keep the quality of service to achieve customer satisfaction the adoption of precedence delivery time - A prospective study)) - البياتي, اميرة شكرولي; العيسى, مصطفى جعفر (Journal of Economics and Administrative Sciences, 2013)
Over application courier company (DHL) to keep the quality of service to achieve customer satisfaction the adoption of precedence delivery time - A prospective study))Become attention to quality is a global phenomenon, and I took organizations and governments around the world attaches special attention, but we can say that quality has become the first function for many organizations, and has become a management philosophy and lifestyle to enable them to stay in the light of environmental variables on subsequent and rapid change, in addition to increasing awareness of consumers of the level ofquality while offering them goods and services t become institutions obliged to review the modalities of conduct; intended to adapt to the competitive environment and customer service to achieve its goals in the survival, growth and profit, and these institutions express delivery companies from this standpoint interviewed study the literature of the field of business administration in the two axes are the attention span of service companies hipping (Plug Alssria) To keep the quality of service, as well as factors affecting the speed of distribution of any delivery on time after crystallization frame philosophical conceptual and review of the above research efforts related, drafted two assumptions to be tested in the courier company DHL in Baghdad (the study sample), in order to diagnose after the company's activities represented operations and supply External service provided and human resources in the dimensions of competition expressed "by the dimension of quality and delivery Kpaadin foundations, cost and flexibility dimensions secondary indicators of quantity and using the method of analysis of each of the simple regression and correlation and Alostoshidh answer and analysis of variance has led the results of hypothesis testing, and analysis and interpretation to the exit conclusion President expressed pursue The company strategy compete based on dimensions of quality and quick delivery runs to win customer satisfaction concluded the study group recommendations, mainly improved the performance level of the courier service from the standpoint of customers, in terms of trying to reduce the price of the services provided and raise their quality and timeliness of delivery of packages and offer new services compared to the services provided by competitors, and the need to develop guiding plates in all service centers include the steps to be followed by customers to receive service and (in more than one language) .. and the company survey studies from time to time in order to identify the arguments and desires of customers....